A Novel Laser-Based Zebrafish Model for Studying Traumatic Brain Injury and Its Molecular Targets - Maria A. Tikhonova; Nikolai A. Maslov; Alim A. Bashirzade; Eugenyi V. Nehoroshev; Vladislav Y. Babchenko; Nadezhda D. Chizhova; Elena O. Tsibulskaya; Anna A. Akopyan; Evgeniya V. Markova; Yi-Ling Yang; Kwok-Tung Lu; Allan V. Kalueff; et al. (MDPI AG, 2022)
Traumatic brain injury (TBI) is a major public health problem. Here, we developed a novel model of non-invasive TBI induced by laser irradiation in the telencephalon of adult zebrafish (Danio rerio) and assessed their behavior and neuromorphology to validate the model and evaluate potential targets for neuroreparative treatment. Overall, TBI induced hypolocomotion and anxiety-like behavior in the novel tank test, strikingly recapitulating responses in mammalian TBI models, hence supporting the face validity of our model. NeuN-positive cell staining was markedly reduced one day, but not seven days, after TBI, suggesting increased neuronal damage immediately after the injury, and its fast recovery. The brain-derived neurotrophic factor (Bdnf) level in the brain dropped immediately after the trauma, but fully recovered seven days later. A marker of microglial activation, Iba1, was elevated in the TBI brain, albeit decreasing from Day 3. The levels of hypoxia-inducible factor 1-alpha (Hif1a) increased 30 min after the injury, and recovered by Day 7, further supporting the construct validity of the model. Collectively, these findings suggest that our model of laser-induced brain injury in zebrafish reproduces mild TBI and can be a useful tool for TBI research and preclinical neuroprotective drug screening.